2022
DOI: 10.1186/s12915-022-01413-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel nuclear receptor subfamily enlightens the origin of heterodimerization

Abstract: Background Nuclear receptors are transcription factors of central importance in human biology and associated diseases. Much of the knowledge related to their major functions, such as ligand and DNA binding or dimerization, derives from functional studies undertaken in classical model animals. It has become evident, however, that a deeper understanding of these molecular functions requires uncovering how these characteristics originated and diversified during evolution, by looking at more specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…We also identified a representative of the NR6 subfamily in M. galloprovincialis , which was notable because bivalve mollusks were supposed to have lost all members of this subfamily in the course of evolution [10,17]. In addition, the phylogeny of the canonical M. galloprovincialis NRs revealed a representative of the NR7 subfamily [35,36]. Separate phylogenetic analyses further allowed us to define two M. galloprovincialis members of the 2DBD NR subfamily, which have previously been identified, for example, in C. gigas and the trematode worm Schistosoma mansoni , as well as a single M. galloprovincialis member of the NR0 subfamily, as previously documented, for example, in C. gigas (electronic supplementary material, figure S3) [10,17].…”
Section: Resultsmentioning
confidence: 99%
“…We also identified a representative of the NR6 subfamily in M. galloprovincialis , which was notable because bivalve mollusks were supposed to have lost all members of this subfamily in the course of evolution [10,17]. In addition, the phylogeny of the canonical M. galloprovincialis NRs revealed a representative of the NR7 subfamily [35,36]. Separate phylogenetic analyses further allowed us to define two M. galloprovincialis members of the 2DBD NR subfamily, which have previously been identified, for example, in C. gigas and the trematode worm Schistosoma mansoni , as well as a single M. galloprovincialis member of the NR0 subfamily, as previously documented, for example, in C. gigas (electronic supplementary material, figure S3) [10,17].…”
Section: Resultsmentioning
confidence: 99%
“…The absence of KR55 in 2DBD-NRs suggests that the first class I salt bridge is absent from 2DBD-NRs. The first salt bridge of class I NRs was missing in Branchiostoma lanceolatum NR7 (of note, NR7 was recently used to describe another group of NRs other than 2DBD-NRs, see next section) [ 52 ]. Experiments showed that 2DBD-NRs could form homodimers in a DNAindependent way [ 14 , 51 ], which suggests that other factors may be involved in regulation of homodimerization of 2DBD-NRs.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…Previously, we suggested placing 2DBD-NRs in a new NR subfamily (NR subfamily 7, NR7) [ 12 , 14 ] and this was accepted by some other studies [ 16 , 54 , 55 ]. However, NR7 was recently used to describe NRs [ 52 ] previously known as NR8 members [ 55 ] and amphioxus NR1Hs [ 33 , 56 ]. To avoid confusion of 2DBD-NRs with other NRs named as NR7, we propose to designate2DBD-NRs as a subfamily instead of using NR7.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…Previously, we suggested placing 2DBD-NRs in a new NR subfamily (NR subfamily 7, NR7) when we discovered the 2DBD-NRs [6,8] and this was accepted by some other studies [10,44,45]. However, NR7 was recently used to describe NRs [46] previously known as NR8 members [45] and amphioxus NR1Hs [27,47]. To avoid confusion of 2DBD-NRs with other NRs named as NR7, our proposal keeps 2DBD-NRs as a subfamily instead of using NR7.…”
Section: ) Nr Subfamilies Are Designated By Arabic Numerals (Nr7 2dbd...mentioning
confidence: 99%